The Construction Industry in India: Market Study and Strategy - Pande, Gaurav (2010)
The total size of the construction industry in India is USD 125 billion, with the infrastructure sector contributing nearly 60 percent to the total market. However, the major growth is expected to be experienced in the real estate sector, with an estimated compound annual growth rate (CAGR) of 30 percent till 2015. The main growth drivers of the industry are the booming economy, rising urbanisation, leading to increase in housing and commercial space, and favourable government initiatives to promote the industry. However, the lack of modern technology and skilled human resource can hinder the future growth of the Indian construction industry, as it directly impacts the productivity, quality and the cost of construction. Public-Private Partnerships (PPPs) are emerging as a new trend in the market for an efficient mode of financing capital intensive projects, thereby providing lucrative investment opportunity and attracting high foreign direct investments (FDIs). Also, the concept of sustainability is gaining momentum due to increasing concern of global warming, with most of the effort driven towards the energy consumption in the real estate sector (commercial and residential). The value chain is different for real estate and infrastructure sectors. On one hand, the developers in the real estate sector have no engineering capabilities and thus, use an external engineering consultancy firm for such services. On the other hand, the developers in the infrastructure sector are huge and have integrated engineering, procurement and construction (EPC) capabilities. However, the key initiator and decision maker in infrastructure projects is the government. The main developers in the real estate sector are DLF, Unitech, Parsavnath, K Raheja and Ansal Properties. The main EPCs in the infrastructure sector are Larsen and Toubro, Gammon, GMR Infrastructure, IRCON and Hindustan Construction Company. The key success strategy for an engineering consulting firm operating in India is to focus and continuously improve upon its technical capabilities and knowledge base, which can be done by utilising efficient knowledge management tools and strategies. The more value created in the whole delivery process, both for the client and the consulting firm, the better would be the reputation of the consulting firm in the market.